Early observations on the impact of a healthcare worker COVID-19 vaccination programme at a major UK tertiary centre. Issue 1 (July 2021) - Garvey, Mark I.; Wilkinson, Martyn A C; Holden, Elisabeth; Shields, Adrian; Robertson, Alastair; Richter, Alex; Ball, Simon
Highlights: The pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the rapid development of multiple vaccines which have been rolled out worldwide. In the first phase of the UK vaccine programme, HCWs were amongst the first to be vaccinated. This offered an opportunity to observe the effect in one the largest groups of HCWs in the UK. Our preliminary data suggests one dose of the vaccine is affording some protection and the probability of a member of staff testing positive for SARS CoV-2 given that they have been vaccinated with one dose is lower than for staff who have not been vaccinated. However, a proportion of our vaccinated HCW are still acquiring SARS-CoV-2, an important message being that one dose of the vaccination will not prevent individuals from getting COVID-19 and potentially transmitting it. We conclude that it is imperative staff remain vigilant once they are vaccinated, due to the ongoing potential for onwards transmission to patients and other HCWs.